1943
DOI: 10.2134/agronj1943.00021962003500010009x
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Drought Tests of Some Pasture and Turf Grasses1

Abstract: \1 [HERE hot, dry winds blow frequently during the growmg IV season, many plants die even though soil moisture has not been reduced to the wilting point. Such desiccation of plants is called atmospheric drought and has not received as much attention as soil, or edaphic drought. Although atmospheric drought seldom affects growth and duration of grasses in the Great Lakes region, these data on atmospheric drought are submitted in the hope that they will be of interest to those concerned with the physiology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1954
1954
1966
1966

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Excessive death of tillers during a hot or dry spell could occur, leading to a substantial opening of the pasture and to a reduction of its productivity. The results presented support the earlier findings by Dexter (1937) and Carroll (1942) that nitrogen fertilisation during summer reduced survival of plants of various graminaceous species in U.S.…”
Section: Influence Of Shadingsupporting
confidence: 90%
See 1 more Smart Citation
“…Excessive death of tillers during a hot or dry spell could occur, leading to a substantial opening of the pasture and to a reduction of its productivity. The results presented support the earlier findings by Dexter (1937) and Carroll (1942) that nitrogen fertilisation during summer reduced survival of plants of various graminaceous species in U.S.…”
Section: Influence Of Shadingsupporting
confidence: 90%
“…Heyne and Brunson 1940;Carroll 1942;Julander 1945;Iljin 1957). Although Levitt (1951) concluded that frost, drought (i.e.…”
Section: Introductionmentioning
confidence: 99%